Treatment patterns, adverse events, healthcare resource use and costs among commercially insured patients with mantle cell lymphoma in the United States. (8th October 2019) - Kabadi, Shaum M.; Near, Aimee; Wada, Keiko; Burudpakdee, Chakkarin
Abstract: Introduction: There are limited data on treatment patterns, adverse events (AEs), and economic burden in younger, commercially insured patients treated for mantle cell lymphoma (MCL). Methods: Adults with ≥1 treatment for MCL between 1 November 2013‐31 December 2017 were identified from IQVIA Real‐World Data Adjudicated Claims‐US; index date was first treatment. Patients carried ≥1 MCL diagnosis, were newly treated, and were enrolled continuously for ≥12 months prior to and ≥30 days following index. Patients receiving the four most common MCL regimens were included. Measures included frequency of incident AEs, resource use, and costs overall and by number of AEs. Adjusted logistic regression and generalized linear modeling evaluated risk of hospitalization and all‐cause costs per patient per month (PPPM). Results: Two thousand five hundred and nine treated patients had a drug‐specific code and were classified to a specific treatment regimen. Of those patients, 1785 patients received at least one of the four most commonly used MCL regimens (R‐CHOP, rituximab monotherapy, B‐R, and ibrutinib) at some point over follow‐up (median 23 months). R‐CHOP was the most common regimen observed in the first line (26%), followed by rituximab monotherapy (19%), B‐R (15%), and ibrutinib (5%). The median age was 57 years; median Charlson Comorbidity Index was 0. Among patients receiving the four most common regimens, 63% of patients experienced ≥1 incident AE (R‐CHOP 77%, B‐R 58%, and ibrutinib 52%). An increasing number of incident AEs was associated with increased hospitalization risk (odds ratio = 2.4; 95% Confidence Interval [CI] 2.1‐2.7) and increased mean costs PPPM (cost ratio = 1.1; 95% CI 1.1‐1.2). Discussion: This is the largest study describing treatment patterns and clinical and economic impact of MCL treatment. The most common regimens were R‐CHOP, rituximab monotherapy, B‐R, and ibrutinib. The majority of treated patients experienced at least one incident AE, with hospitalization risk and all‐cause costs increasing as the number of AEs increased. Abstract : This retrospective cohort study utilizing data from IQVIA Real‐World Data Adjudicated Claims‐US is the largest study describing treatment patterns and clinical and economic impact of MCL treatment. The most common regimens were R‐CHOP, rituximab monotherapy, B‐R, and ibrutinib. The majority of treated patients experienced at least one incident AE, with hospitalization risk and all‐cause costs increasing as the number of AEs increased.